Vertical Windmills as a Charging Station Solution for Pantai Kondang Merak - Muhiban Syabani (Universitas Sahid Surakarta, 2024)
Abstract: Kondang Merak Beach is a popular tourist destination visited by tourists for tours. The average tourist comes from urban areas who are already familiar with electronic devices for activities of daily life. Based on the facts from the initial survey, it was found that the obstacle that is often faced by tourist visitors is the electricity network that has not been accessed by PLN. Electricity is needed by visitors to recharge gadget batteries and for other purposes. The electricity supply so far has been obtained from diesel generators which only operate at night. Therefore, a power supply that can operate 24 hours is needed, especially when many visitors come during the day. We can take advantage of the potential energy available on the beach such as wind, sun, and ocean waves (Pitriadi et al., 2018). Keywords: vertical windmill, generator, charging station